Benefits of dry needling of myofascial trigger points on autonomic function and photoelectric plethysmography in patients with fibromyalgia syndrome. Issue 3 (June 2020) - Castro-Sánchez, Adelaida María; Garcia-López, Hector; Fernández-Sánchez, Manuel; Perez-Marmol, José Manuel; Leonard, Guillaume; Gaudreault, Nathaly; Aguilar-Ferrándiz, María Encarnación; Matarán-Peñarrocha, Guillermo Adolfo
Background: Fibromyalgia syndrome (FMS) is a condition characterised by the presence of chronic, widespread musculoskeletal pain, low pain threshold and hyperalgesia. Myofascial trigger points (MTrPs) may worsen symptoms in patients with FMS. Objective: The purpose of this randomised controlled trial was to compare the effects of dry needling and transcutaneous electrical nerve stimulation (TENS) on pain intensity, heart rate variability, galvanic response and oxygen saturation (SpO2 ). Methods: 74 subjects with FMS were recruited and randomly assigned to either the dry needling group or the TENS group. Outcomes measures (pain intensity, heart rate variability, galvanic skin response, SpO2 and photoplethysmography) were evaluated at baseline and after 6 weeks of treatment. 2×2 mixed-model analyses of variance (ANOVAs) were performed. Results: The mixed-model ANOVAs showed significant differences between groups for the sensory dimension of pain, affective dimension of pain, total dimension of pain, visual analogue scale (VAS) and present pain intensity (PPI) (P=0.001). ANOVAs also showed that significant differences between groups were achieved for very low frequency power of heart rate variability (P=0.008) and low frequency power (P=0.033). There were no significant differences in dry needling versus TENS groups on the spectral analysis of the photoplethysmography and SpO2 . Conclusions: This trial showed that application of dry needling therapy and TENS reduced pain attributable to MTrPs in patients with FMS, with greater improvements reported in the dry needling group across all dimensions of pain. Additionally, there were between-intervention differences for several parameters of heart rate variability and galvanic skin responses. Trial registration number: NCT02393352